The Influence of Fatherless on Aggression Behavior in Adolescents - Ismalandari Ismail; Sitti Murdiana; Rahmat Permadi (PT ARRUS Intelektual Indonesia, 2024)
Adolescence is a transitional age from childhood to adulthood so it can give rise to psychological problems, one of which is aggressive behavior. Teenagers give rise to brawling, bullying and other juvenile delinquency. Teenagers pay less attention to the norms or rules that apply in their environment and behave arbitrarily, which is quite disturbing to society. There are many factors that cause aggressive behavior, namely economic problems and the absence of a father figure in one's development. The absence of a father figure (Fatherless) will affect teenagers' psychology, including channeling their emotions and showing aggressive behavior. The aim of this research is to find out how fatherlessness influences adolescent aggressive behavior. The research method used is a quantitative research method using a scale in collecting data. The father's role scale was adapted from aspects according to Lamb (2010) which include paternal accessibility, paternal engagement, and paternal responsibility. The aggressive tendencies scale was adapted from Buss and Perry (1992), namely based on the forms of physical aggression, verbal aggression, anger and hostility. The results of research conducted on 200 teenagers show that there is a positive influence between fatherlessness and aggressive behavior in teenagers. The magnitude of the correlation between fatherlessness and aggressive behavior is 0.022 with a significance level or p of 0.038, a coefficient with a positive sign indicates a positive direction of correlation. The hypothesis which states that there is a positive influence between fatherlessness and aggressive behavior is accepted.